Single center experience of ICD implantation in pediatric age. (24th May 2021) - Fumanelli, J; Reffo, E; Castaldi, B; Sirico, D; Di Salvo, G; Leoni, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Despite sudden cardiac death (SCD) is a rare phenomenon in pediatric age, the use of the implantable defibrillator (ICD) is progressively increasing in consideration of its life-saving role both in primary and in secondary prevention. Our work aims at evaluating our pediatric population from the point of view of distribution according to heart disease, indication and implantation technique. We also want to verify the protective role of the device in terms of SCD prevention, acute and chronic complications and to evaluate the role played by the device as a bridge to transplantation. METHODS The retrospective study includes patients under the age of 18 underwent ICD implantation, following the guidelines and recommendations currently in force, in the time period between March 2000 and July 2020. Each device has been programmed in a personalized way based on age and cardiac pathology. The subjects were divided into three groups depending on the cardiac pathology. All patients were then followed-up by evaluating the appropriate shocks, the acute and chronic complications, especially the inappropriate shocks. RESULTS The study group includes 55 subjects (41 males and 12 females) with a mean age of 14 ± 4 years and a mean follow-up time of 6.2 years. Thirty subjects had cardiomyopathy (CM), 15 electrical disease (ED) and 10 congenital heart disease (CHD) respectively. We used three different implantation technique (endocavitary, subcutaneus and hybrid technique) depending on the size of the patient and the cardiac anatomy. There is no gender difference as regards the indication to the implant in primary/secondary prevention (67% in secondary prevention vs 33% in primary prevention). CHD and CM are mostly implanted in primary prevention. The rate of appropriate shocks in secondary prevention is higher than that in the primary one regardless of the disease. Thirty-eight percent of patients received appropriate shock, of which 66.7% were patients who had received defibrillator as a bridge to heart transplant. Two patients (3.6%) received inappropriate shocks on supraventricular tachycardia. There were no acute post-implantation complications. None dysfunctions or ruptures of the shock catheter or episodes of T wave oversensing took place. Peri-procedural and post-transplant mortality is zero, except for a deceased subject awaiting transplantation due to congestive heart failure. CONCLUSIONS The study confirmed the protective role of the device, in terms of prevention of sudden cardiac death, and its relevance as bridge to heart transplantation in pediatric age. An implant technique adequate to the size, age and heart disease of the patient associated with an adequate programming of the device significantly reduced inappropriate shocks in our patients.